Allergic rhinitis. Perpetual problem and current solutions - O. M. Kurbacheva (Медицинский совет, 2015)
The past 30 years have seen an overall increase in the prevalence of allergic diseases (AD) among which allergic rhinitis (AR) is one of the most common. The disease produces a significant impact on physical and mental health of patients, and is a heavy social burden. In the US, the number of patients with AR is 25-30 million people, while AD are registered in more than 40 million people. In England, the prevalence of AR is 16%, in Denmark - 19%, in Germany - 13--17%.